C++ recipes : a problem-solution approach - Sutherland, Bruce (Video game developer) (Expert's voice in C++., 2015)
C++ Recipes: A Problem-Solution Approach is Apress' solution for those C++ programmers looking for a handy code cookbook reference guide. It covers the latest C++ 14 as well as some of the code templates available in the latest Standard Template Library (STL). In this handy reference, you'll find numbers, strings, dates, times, classes, exceptions, streams, flows, pointers and more. Also, you'll see various code samples, templates for C++ algorithms, parallel processing, multithreading and numerical processes. These have many applications including game development, big data analytics, financial engineering and analysis, enterprise applications and more. A wealth of STL templates on function objects, adapters, allocators, and extensions are also available. This is a "must have", contemporary reference for your technical books library.